A novel ultrasonographic assisted technique for desmotomy of the palmar/plantar annular ligament in horses. Issue 5 (10th February 2017) - Espinosa, Pablo; Nieto, Jorge E.; Snyder, Jack R.; Galuppo, Larry D.; Katzman, Scott A.
Abstract: Objectives: To describe an ultrasound assisted technique for desmotomy of the palmar/plantar annular ligament (PAL), determine its efficacy and intraoperative complications. Study design: Cadaveric and in vivo study. Animals: Cadaveric limbs (n = 12), adult horses (n = 4), and clinical cases (n = 2). Methods: Ultrasound assisted desmotomy of the palmar/plantar annular ligament (UAD‐PAL) was performed in cadaveric limbs and in standing horses with the operated limb placed in a distal limb splint. The procedure was performed under general anesthesia and was followed by tenoscopic examination in 2 clinical cases. A hook knife was developed for the procedure. Complete transection was assessed by postmortem dissection (10 forelimbs, 10 hindlimbs) and tenoscopic examination (1 forelimb, 1 hindlimb). Thickness of PAL, surgery time, other intraoperative parameters and complications associated with the procedure were recorded. Results: Complete PAL transection was accomplished in 20/22 limbs. No iatrogenic damage to adjacent intrathecal structures was identified in any case. The instrument was correctly positioned on the first attempt in 19/22 cases. The most common intraoperative complication was inadvertent subcutaneous placement of the instrument (n = 2). Significant thickening of the PAL (3 mm) was present in 1/2 limbs in which complete transection was not achieved. Conclusions: UAD‐PAL with the custom‐made hook knife was effective at transecting the PAL with minimal intraoperative complications. The procedure can be performed in standing sedated horses. Another method should be considered in horses with thickened PAL.